2020
DOI: 10.1007/s11420-020-09794-0
|View full text |Cite
|
Sign up to set email alerts
|

Public Interest in Knee Replacement Fell during the Onset of the COVID-19 Pandemic: A Google Trends Analysis

Abstract: Background: The COVID-19 pandemic significantly altered medical practice and public behavior in the USA. In spring of 2020, elective surgery including most joint replacement was suspended and much of the public asked to stay at home. As elective surgery resumes, it is unknown how the public will respond. Questions/Purposes: We sought to describe public interest in knee replacement during the onset of the COVID-19 pandemic. Methods: Google Trends was used to obtain the daily number of searches for "knee replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…Several surveys and online trend analysis reported decreased interest of patients in hip and knee replacement surgeries. 16,17 While at one end, patients may opt to precautionarily delay elective surgeries as much as they can and on the other, ones with end stage hip or knee arthritis who continue to suffer with pain and disabilities needing arthroplasty want to get operated as early as possible. Ensuring safety of both patients and staff is paramount and delivering optimal results with minimum complications is a challenging task.…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys and online trend analysis reported decreased interest of patients in hip and knee replacement surgeries. 16,17 While at one end, patients may opt to precautionarily delay elective surgeries as much as they can and on the other, ones with end stage hip or knee arthritis who continue to suffer with pain and disabilities needing arthroplasty want to get operated as early as possible. Ensuring safety of both patients and staff is paramount and delivering optimal results with minimum complications is a challenging task.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of the internet for the access to health-care information has become an increasingly important source of health-related information for consumers which has allowed individuals to obtain medical information rapidly, conveniently, and privately [14,15]. With the growth in the use of the internet as a primary source for the acquisition and dissemination of health information, internet search tools such as Google Trends have emerged as important sources of real-time information of online search patterns and can be useful in determining patient's interest in elective hand surgery over time [16][17][18]. The objective of this study is to use Google Trends to track online interest in elective hand surgery in the United States during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the medical relevance of Google Trends analytics in the spread of influenza in the U.S.-similar to our findings, changes in public interest were evident prior to increasing case numbers and hospitalizations [ 16 , 17 ]. Likewise, Landy et al were able to describe a decline in public interest in knee replacements in the U.S. using Google Trends during the first wave of SARS-CoV-2 infections [ 12 ]. However, in this study it remained unclear whether this decrease reflected in changes in patient behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Public interest was investigated using Google Trend analysis as previously described [ 12 ]. In short, daily relative search frequencies for knee pain, knee osteoarthritis and knee replacement were assessed for the entire year 2020 in Germany and the UK.…”
Section: Methodsmentioning
confidence: 99%